2010
DOI: 10.1002/ijc.25287
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal and hypopharyngeal carcinoma risk among immigrants in Sweden

Abstract: Environmental exposures, particularly infection with Epstein‐Barr virus (EBV) and tobacco, are known risk factors for oral cancer. Studies in migrants may provide valuable insight into the environmental and genetic etiology of cancer. We wanted to define nasopharyngeal and hypopharyngeal carcinoma among immigrants in Sweden. The nationwide Swedish Family‐Cancer Database (FCD) was used to calculate standardized incidence ratios (SIRs) for nasopharyngeal and hypopharyngeal carcinomas among the first‐generation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…However, no direct data is available to show the trend of smoking prevalence among immigrants. 19,20,27 An increasing incidence of breast cancer in many non-European countries from where people migrated to Sweden was reported. 28 Simultaneously, our previous experience showed that the overall breast cancer incidence was increased in immigrants, in parallel with the length of stay in Sweden, whereas the effect of age at immigration was not explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no direct data is available to show the trend of smoking prevalence among immigrants. 19,20,27 An increasing incidence of breast cancer in many non-European countries from where people migrated to Sweden was reported. 28 Simultaneously, our previous experience showed that the overall breast cancer incidence was increased in immigrants, in parallel with the length of stay in Sweden, whereas the effect of age at immigration was not explored.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Age-specific incidence rates estimated among native Swedes within the FCD were selected as reference for which was served to calculate expected number of cases. To catch the maximum number of cases during five decades of residence in Sweden, immigrants were also classified according to country of origin-and sex-specific colorectal, lung, breast and prostate cancers risk based on the results presented in Table 1 (high-risk: SIR significantly increased; low-risk: SIR significantly decreased and other: nonsignificant SIR).…”
Section: Methodsmentioning
confidence: 99%
“…Like our previous studies, [25][26][27] we calculated standardized incidence ratios (SIRs) and standardized mortality ratios (SMRs) as the ratio of observed to expected number of cases and deaths. The expected number of cases and deaths were calculated in 5-year age groups and in 10-year intervals for the years between 1958 and 2008.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental factors are important as migrant studies have shown that the rates decline to intermediate rates between the countries of origin and countries of residence. (Yu and Hussain 2009;Mousavi et al, 2010). Low economic social status, an indirect indicator to exposures of the risk factors has also been reported to be associated with NPC.…”
Section: Discussionmentioning
confidence: 99%